Predictors for HIV testing among Chinese workers in infrastructure construction enterprises in Kenya - Wenjuan Zhou; Wenyu Deng; Junfei Luo; Yin Bai; Zeyi He; Honghong Wang (BMC, 2021)
Abstract Background There are increasing Chinese migrants in sub-Saharan Africa currently. Most of them are engaged in infrastructure construction. Research has shown that they stay at particular risk of HIV and are recommended for HIV testing. However, their HIV testing behavior, and its relevant factors, have not been researched among them by now. This study describes the recent HIV testing behavior and relevant factors among Chinese migrant workers in Kenya. Methods A cross-sectional survey was conducted among 110 male Chinese workers from six different Chinese infrastructure construction enterprises in Kenya. Furthermore, a two-stage cluster random sampling method was used to select participants. We used a questionnaire that included HIV testing history, demographic characteristics, and putative multilevel facilitators of HIV testing. Logistic regression was used to explore the predictors of recent HIV testing behavior among Chinese migrant workers in Kenya. Result Of the 110 participants, 30 (27.27%) were tested for HIV in the recent year. All participants were male, and the majority were married (73.2%). The mean age was 37.49 years (SD = 9.73; range: 23 to 63), and a considerable proportion refused to answer questions about transactional sexual behaviors in the last year. Most were able to obtain HIV-related information (91.8%) and were exposed to HIV-related information in the last year (68.2%), but only 47.6% had sufficient HIV knowledge. Nearly one-fifth of them believed that selling sex and paying for sex is acceptable. Multiple logistic regression analysis indicated that participants who could accept the 'pay for sex' (OR: 2.74; 95% CI: 1.02, 7.36) and exposed to HIV related information (OR: 4.75; 95% CI: 1.29, 17.44) were more likely to test for HIV in the recent 1 year. Conclusion Higher current HIV test rates were associated with a more open sexual attitude towards paying for sex and being exposed to HIV-related information in the last year among Chinese workers in Kenya. More specific attention to HIV should be attached to this population to increase the rate of HIV testing among them.